Immunohistochemistry and gene expression of GLUT1, RUNX2 and MTOR in reparative dentinogenesis. (17th December 2019) - Takeuchi, Ryosuke; Ohkura, Naoto; Yoshiba, Kunihiko; Tohma, Aiko; Yoshiba, Nagako; Edanami, Naoki; Shirakashi, Mari; Belal, Razi Saifullah Ibn; Ohshima, Hayato; Noiri, Yuichiro
Abstract: Objectives: To determine glucose transporter 1 (GLUT1) and runt‐related transcription factor 2 (RUNX2) expression during reparative dentinogenesis after pulpotomy with mineral trioxide aggregate (MTA) capping. Subjects and methods: Eight‐week‐old male Wistar rats were used. Pulp of the upper left first molar was exposed and capped with MTA. The upper right first molar of the same animal was used as a control. After collecting molars at various time points, GLUT1, RUNX2 and mammalian target of rapamycin (MTOR) were examined by immunohistochemistry. mRNA levels of Slc2a1 (encoding GLUT1), Runx2, Nestin and Mtor were determined by real‐time PCR. Results: Pulp exhibited progressive formation of reparative dentine lined with GLUT1‐ and MTOR‐immunoreactive odontoblast‐like cells at 5 days after pulpotomy. RUNX2 was detected in nuclei of most pulp tissue cells at day 5 after pulpotomy. Double immunofluorescence staining revealed GLUT1 immunoreactivity on odontoblast‐like cells positive for Nestin or RUNX2, 5 days after pulpotomy. Slc2a1, Runx2, Nestin and Mtor mRNA levels were significantly upregulated on days 3–5 after pulpotomy. Conclusions: After rat molar pulpotomy, dental pulp induced formation of reparative dentine with colocalization of GLUT1 and Nestin or RUNX2. Moreover, mRNA levels of Slc2a1, Runx2, Nestin and Mtor were significantly upregulated in pulpotomized dental pulp.